Otoritas Kristus dalam Pendidikan di Era AI: Analisis Teologis-Pedagogis Peran Guru PAK dalam Menghadapi Degradasi Moral Peserta Didik - Edwin Ballu (Institut Agama Kristen Negeri Toraja, 2025)
Abstract: Technological advances with the presence of Artificial Intelligence (AI) have had a major impact on the world of education. Technological advances also impact the character of students, with a tendency for moral degradation to increase. This condition poses a challenge for Christian Religious Education, particularly the affirmation of Christ's authority (the Bible) as the basis of teaching. This study aims to analyze the theological-pedagogical presence of Christian Religious Education teachers in their roles and impacts in responding to moral degradation in the world of education nationally. The method used in this study is a qualitative method based on literature studies and analysis of national education policy documents, and educational theory with a Biblical basis as its evaluation framework. The presence of Christian Religious Education teachers is not merely an agent of knowledge transformation. However, the presence of Christian Religious Education teachers must be present in a prophetic, pastoral, and behavioral change role based on the truth of God's word. The presence of AI is an opportunity to develop strengthening pedagogical, spiritual, social, and professional competencies in shaping students who know, love, and live according to God's word. The presence of AI does not replace the authority of Christ through exemplary behavior, ethical wisdom, and relevant and liberating contextual learning. Abstrak : Kemajuan teknologi dengan kehadiran Artificial Intelligence (AI), berdampak besar bagi dunia pendidikan. Kemajuan teknologi, berdampak pula pada karakter peserta didik, ada kecenderungan meningkatnya degradasi moral. Kondisi ini menjadi tantangan tersendiri bagi Pendidikan Agama Kristen (PAK), khususnya penegasan otoritas Kristus (Alkitab), sebagai dasar pengajaran. Adapun Penelitian ini bertujuan untuk menganalisis kehadiran Guru PAK secara teologis-pedagogis dalam peran dan dampaknya dalam merespon degradasi moral dalam dunia pendidikan secara nasional. Metode yang digunakan dalam penelitian ini yaitu metode kualitatif berbasis studi literatur dan analisis dokumen kebijakan pendidikan nasional, dan teori pendidikan dengan landasan Alkitan sebagai kerangka evaluasinya. Kehadiran guru PAK bukan semata sebagai agen transformasi pengetahuan. Akan tetapi, kehadiran guru PAK harus hadir dalam peran profetik, pastoral, dan perubahan perilaku dengan berdasar pada kebenaran firman Tuhan. Kehadiran AI menjadi peluang dalam pengembangan penguatan kompetensi pedagogik, spiritual, sosial, dan profesional yang dalam membentuk peserta didik yang mengenal, mengasihi, dan hidup sesuai firman Tuhan. Kehadiran AI tidak menggantikan otoritas Kristus melalui keteladanan, kebijaksanaan etis, dan pembelajaran kontekstual yang relevan dan membebaskan.